Glucose interpretation meaning and action (GIMA): Insights to blood glucose user interface interpretation in type 1 diabetes - Rujiravee Kongdee; Bijan Parsia; Hood Thabit; Simon Harper (Digital Health)
Background Current glucose monitoring user interfaces (UIs) are problematic for people with Type 1 Diabetes Mellitus (T1DM) in maintaining recommended blood glucose levels effectively. However, there is a lack of in-depth investigation into this problem when these individuals interpret and make real-time decisions based on the glucose monitoring devices they use daily. Objectives We aim to investigate problems associated with glucose monitoring UIs by observing users’ interpretation and decision-making while reading their Continuous Glucose Monitoring (CGM), Flash Glucose Monitoring (Flash) or Self-monitoring of Blood Glucose (SMBG). Methods A mixed-method study was conducted. The Think Aloud protocol was used to capture participants’ decision-making process while reading various device UIs. Their responses were evaluated using standard clinical guidance to assess their accuracy. Additionally, a survey was distributed to gather their perceptions of self-management practices. Results Twenty-seven participants (17 patients and 10 carers) were recruited. Interpretation accuracy averaged 38 . 0%  ±  11 . 1% for CGM, 39 . 5%  ±  8 . 8% for Flash, and 33 . 3%  ±  7 . 8% for SMBG group. Treatment action accuracy was 21 . 5%  ±  15 . 6% for CGM, 21 . 2%  ±  14 . 0% for Flash, and 18 . 0%  ±  13 . 2% for SMBG group. Despite this, 75 . 0% of all participants expressed very high confidence in their self-management. Conclusions Interpreting and making decisions using glucose monitoring UIs remains significantly challenging for people with T1DM despite their self-perceived performance. Improving such UIs is crucial to reduce misinterpretation and help these individuals make better treatment decisions without relying on their potentially inaccurate interpretations.